Potensi Antibakteri Ekstrak Rumput Laut Terhadap Bakteri Penyakit Kulit Pseudomonas aeruginosa, Staphylococcus epidermidis, dan Micrococcus luteus - Siregar, Angelina Ferawaty; Sabdono, Agus; Pringgenies, Delianis (977-2407769)
Along with the increasing resistance of bacteria in the health world, it is necessary discover a new drug. Sources of new antibacterial bioactive compounds can be obtained from seaweeds. The purposes of the research were to determine the antibacterial activity of crude extract seaweed againts the skin disease bacteria, Pseudomonas aeruginosa, Staphylococcus epidermidis and Micrococcus luteus, and to identify classes of compounds contained in crude extract of seaweed. This research was done from January to Mei 2012. Seaweeds sampling (Caulerpa sp, Eucheuma sp, Gracilaria sp dan Sargassum sp) was conducted in territorial water of Jepara. Extraction process and analysis of bioactive compound of crude extracts was conducted at Laboratory, Marine Science Department, Diponegoro University, Semarang. Test antibacterial activity was conducted at Medicine Laboratory, Ungaran. The method used in this research was experimental laboratories. Extraction process was conducted with solid-liquid extraction method. Extract were tested for antibacterial activity by agar diffusion method according to Kirby-baurer. Based on the antibacterial activityâ€™s assay, 12 extracts which have antibacterial activity against test bacteria P. aeruginosa, S. epidermidis and M. luteus were obtained the 12 seaweed extracts the highest consentration of inhibition zone was 200 Âµg/disk in ethyl acetate extract of the Sargassum sp was the most active extracts against bacteria P. aeruginosa and M. luteus, while the methanol extract of Sargassum sp was the most active extracts against the bacteria S. epidermidis. Steroids was the most dominant compounds on all of 12 seaweed extracts.